Particulate matter phagocytosis induces tissue factor in differentiating macrophages. Issue 1 (8th April 2015) - Milano, M.; Dongiovanni, P.; Artoni, A.; Gatti, S.; Rosso, L.; Colombo, F.; Bollati, V.; Maggioni, M.; Mannucci, P. M.; Bertazzi, P. A.; Fargion, S.; Valenti, L.
Abstract: Airborne exposure to particulate matter with diameter < 10 mcM (PM10 ) has been linked to an increased risk of thromboembolic events, but the mechanisms are not completely understood. The aim of this study was to evaluate the effect of PM10 phagocytosis on the release of procoagulant molecules in human differentiating macrophages, and that of PM10 inhalation in an experimental model in rats. Human monocytes were separated from the peripheral blood by the lymphoprep method, differentiated in vitro and treated with standard PM10 or vehicle. Sprague–Dawley rats were instilled intratracheally with PM10 or vehicle alone. The outcome was expression of proinflammatory genes and of tissue factor (TF). In human differentiating macrophages, PM10 exposure upregulated inflammatory genes, but most consistently induced TF mRNA and protein levels, but not TF protein inhibitor, resulting in increased TF membrane expression and a procoagulant phenotype. Differentiation towards the anti‐inflammatory M2 phenotype inhibited PM10 ‐mediated TF expression. TF induction required phagocytosis of PM10, whereas phagocytosis of inert particles was less effective. PM10 phagocytosis was associated with a gene expression profile consistent with intracellular retention of iron, inducing oxidative stress. Both PM10 and iron activated the stress kinases ERK1/2 pathway, involved in the induction of TF expression. In rats, alveolar exposure to PM10 was associated with pulmonary recruitment of inflammatory cells and resulted in local, but not systemic, induction of TF expression, which was sufficient to increase circulating TF levels. In conclusion, TF induction by differentiating lung macrophages, activated following phagocytosis, contributes to the increased risk of thromboembolic complications associated with PM10 exposure. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Here we show that in human differentiating macrophages, particulate matter with diameter < 10 mcM (PM10 ) exposure induces tissue factor (TF) and a procoagulant phenotype. This process is dependent on phagocytosis and the activation of stress pathways, and is abolished in differentiated anti‐inflammatory macrophages. In rats, alveolar exposure to PM10 causes the recruitment of inflammatory cells and results in local induction of TF, increasing circulating TF levels. TF induction by differentiating lung macrophages, activated following phagocytosis, contributes to the increased risk of thromboembolic complications associated with PM10 exposure.